2007
DOI: 10.1093/eurpub/ckl275
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol poisoning in Russia and the countries in the European part of the former Soviet Union, 1970 2002

Abstract: Acute alcohol poisoning has now reached unprecedented rates in parts of the ex-USSR with worrying trends among men as well as among women. Effective action by the governments concerned is now essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 26 publications
2
94
0
6
Order By: Relevance
“…These results are consistent with the findings that relationship between alcohol and suicide was stronger for consumption of distilled spirits relative to total level of alcohol consumption) [9]. In a more recent time series analysis Stickley and coauthors concluded that binge drinking had a significant association with the occurrence of suicide in Russia and the magnitude of the relation is the same across the course of the later-tsarist, Soviet, and post-Soviet periods [13,14]. Collectively this evidence provides additional support for the hypothesis that unfavorable mixture of higher overall level of alcohol consumption and binge drinking pattern is a major risk factor for suicide mortality in Russia.…”
Section: Introductionsupporting
confidence: 84%
“…These results are consistent with the findings that relationship between alcohol and suicide was stronger for consumption of distilled spirits relative to total level of alcohol consumption) [9]. In a more recent time series analysis Stickley and coauthors concluded that binge drinking had a significant association with the occurrence of suicide in Russia and the magnitude of the relation is the same across the course of the later-tsarist, Soviet, and post-Soviet periods [13,14]. Collectively this evidence provides additional support for the hypothesis that unfavorable mixture of higher overall level of alcohol consumption and binge drinking pattern is a major risk factor for suicide mortality in Russia.…”
Section: Introductionsupporting
confidence: 84%
“…Our data suggest that binge drinking is more frequent among alcohol dependent men than among alcohol dependent women: 97.0% of men and 58.2% of women reported to drink an equivalent of 150 ml of vodka or more at one occasion. It should be emphasis that the harmful drinking pattern was identified as one of the major contributing factor to high alcohol-related mortality in the former Soviet republics [4,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…There is a common belief that alcohol is a crucial factor in the mortality crisis in the former Soviet Republics [1][2][3][4][5]. In Belarus, for example, it has been estimated that alcohol may be responsible for 28.4% of all male deaths and for 16.4% of female deaths [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Russia ranks among the world's heaviest drinking countries with an annual official consumption rate about 10 litres of pure alcohol per capita, while independent estimates show a figure as high as 17 litres [22,23]. The distinctive trait of Russian drinking culture is a high overall level of alcohol consumption and the heavy episodic (binge) drinking pattern of strong spirits (vodka), leading to an increase in deaths from alcohol poisoning and cardiovascular diseases [24][25][26]. In line with these pieces of evidence, we assume that occasional heavy drinking of vodka in Russia should result in a positive association between vodka sale and liver cirrhosis mortality at the aggregate level.…”
Section: Ye*mentioning
confidence: 99%